2009
DOI: 10.1210/me.2008-0462
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Nongenomic Cross Talk between the Gonadotropin-Releasing Hormone Receptor and Glucocorticoid Receptor Signaling Pathways

Abstract: The GnRH receptor (GnRHR), a member of the G protein-coupled receptor family, is a central regulator of reproductive function in all vertebrates. The peptide hormone GnRH exerts its effects via binding to the GnRHR in pituitary gonadotropes. We investigated the mechanisms of regulation of transcription of the mGnRHR gene in the mouse pituitary gonadotrope L beta T2 cell line by GnRH and dexamethasone (dex). Reporter assays with transfected mGnRHR promoter show that both dex and GnRH increase transcription of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
43
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 64 publications
6
43
2
Order By: Relevance
“…For instance, when overexpressed, unliganded GR has the capacity to bind GRE in vitro (39) and in vivo (40). Recently, Kotitschke and colleagues showed that the transcriptional activation of unliganded GR by gonadotropin-releasing hormone was dependent on MAPK-dependent phosphorylation of GR at S234 residues (the equivalent of S226 in human) (41). We found that S226 was not affected by p38 MAPK blockade, suggesting that GR regulation by MAPK is highly cell specific.…”
Section: Discussionmentioning
confidence: 60%
“…For instance, when overexpressed, unliganded GR has the capacity to bind GRE in vitro (39) and in vivo (40). Recently, Kotitschke and colleagues showed that the transcriptional activation of unliganded GR by gonadotropin-releasing hormone was dependent on MAPK-dependent phosphorylation of GR at S234 residues (the equivalent of S226 in human) (41). We found that S226 was not affected by p38 MAPK blockade, suggesting that GR regulation by MAPK is highly cell specific.…”
Section: Discussionmentioning
confidence: 60%
“…While it has traditionally been accepted that nuclear receptors are activated in response to ligand binding, several reports exist of progesterone and estrogen receptor activation and nuclear activity even in the absence of hormone (21). GR has been reported to be activated by various stimuli in the absence of glucocorticoid ligands (21)(22)(23)(24), and unliganded GR has recently been found to bind directly to and exert a repressive effect on the IL-6 promoter in response to TNF-a in endocervical cells (25). In addition, it has been suggested that breast cancer progression may be associated with an accumulation of GR in the cytoplasm of tumor cells (26).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to activation by steroidal ligands, the GR has also been reported to be activated by various stimuli in the absence of glucocorticoid ligands (43)(44)(45). Ursodeoxycholic acid and the ␤-adrenergic receptor agonists salmeterol and salbutamol were shown to induce GR-dependent transcriptional activity (43,44).…”
mentioning
confidence: 99%
“…Ursodeoxycholic acid and the ␤-adrenergic receptor agonists salmeterol and salbutamol were shown to induce GR-dependent transcriptional activity (43,44). We have recently shown that gonadotropin-releasing hormone (GnRH) results in a selective glucocorticoid-independent increase of mGR phosphorylation and transcriptional activity on an endogenous promoter (45). It was demonstrated that GnRH-induced activation of the GR is dependent on the presence of the GnRH receptor and involves MAPKs (45).…”
mentioning
confidence: 99%
See 1 more Smart Citation